2006
DOI: 10.1176/appi.ps.57.10.1406
|View full text |Cite
|
Sign up to set email alerts
|

Supported Employment Outcomes of a Randomized Controlled Trial of ACT and Clubhouse Models

Abstract: Vocationally integrated ACT and certified clubhouses can achieve employment outcomes similar to those of exemplary supported employment teams. Certified clubhouses can effectively provide supported employment along with other rehabilitative services, and the ACT program can ensure continuous integration of supported employment with clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 51 publications
4
41
0
Order By: Relevance
“…This result is similar to findings reported by Macias et al (2006), who found that assertive community treatment (ACT) for the delivery of supported employment services had a higher retention rate when compared to a clubhouse model (79 vs. 58%). Similarly, Mueser et al (2004) found that approximately 50% of participants assigned to a clubhouse model dropped out within a few weeks, compared to less than 10% of IPS participants.…”
Section: Discussionsupporting
confidence: 90%
“…This result is similar to findings reported by Macias et al (2006), who found that assertive community treatment (ACT) for the delivery of supported employment services had a higher retention rate when compared to a clubhouse model (79 vs. 58%). Similarly, Mueser et al (2004) found that approximately 50% of participants assigned to a clubhouse model dropped out within a few weeks, compared to less than 10% of IPS participants.…”
Section: Discussionsupporting
confidence: 90%
“…A continuous age variable was included to further control for an individual's specific age. A dummy variable for a substance abuse diagnosis was added as a proxy for dual diagnosis Macias et al, 2006), because substance abuse is known to complicate the treatment of severe mental health conditions (Dickey, Fisher, Siegel, Altaffer, & Azeni, 1997). The total number of months a beneficiary was enrolled in Medicaid during the study period was included to account for the increased opportunity an individual has to accumulate cost as the number of enrollment months per member increases (Clark, Samnaliev, & McGovern, 2009;Thomas et al, 2005).…”
Section: Regression Modelsmentioning
confidence: 99%
“…The inclusion of pharmacy data increases the likelihood of identifying individuals with specific pharmacy data for which there is no corresponding diagnosis and for individuals with diagnoses without expected, corresponding pharmacy utilization (Kronick, Bella, & Gilmer, 2009). The CDPS has been validated in the literature as both a predictor of chronic illness (Weir et al, 2008) and as a measure of co-morbidity and health status (Clark et al, 2009;Gilmer et al, 2009;Macias et al, 2006;Thomas et al, 2005). Because the study's population was Medicaid SSI adults, the CDPS+Rx was an appropriate risk adjuster.…”
Section: Regression Modelsmentioning
confidence: 99%
“…ACT teams with vocational support have been reported to have client employment rates of up to 64% (Macias et al 2006). Rates of employment have shown to be higher when Individual Placement and Support protocols are used (Twamley et al 2005).…”
Section: Discussionmentioning
confidence: 99%